2020
DOI: 10.1021/acs.jpca.0c05040
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Dissociation of Ni(acac)2 on Iron by Ab Initio Calculations

Abstract: Among metal β-diketonates, nickel acetylacetonate (Ni(acac) 2 ) has been widely employed as a precursor for many chemical structures, due to its catalytic properties. Here, we investigate, by means of density functional theory (DFT) calculations, the adsorption and dissociation of this complex: after an evaluation of the structural and electronic properties of Ni(acac) 2 , a comparison between different dissociation patterns reveals that the most favorable pattern for the complex adsorbed on iron is different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Cut 2 corresponds to an intermediate situation between cut 1 and cut 3, and its fragmentation energy should also lie between the energies of the other two patterns, according to the results of previous fragmentation analyses carried out for sMoDTC and Ni(acac) 2 . 12 , 34 Indeed, considering the Mo-containing fragment obtained by cut 2 as a doublet leaves the unpaired electron on a sulfur atom, which is more electronegative than molybdenum. This may explain the lower fragmentation energy of cut 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cut 2 corresponds to an intermediate situation between cut 1 and cut 3, and its fragmentation energy should also lie between the energies of the other two patterns, according to the results of previous fragmentation analyses carried out for sMoDTC and Ni(acac) 2 . 12 , 34 Indeed, considering the Mo-containing fragment obtained by cut 2 as a doublet leaves the unpaired electron on a sulfur atom, which is more electronegative than molybdenum. This may explain the lower fragmentation energy of cut 2.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that this phenomenon also occurs for the dimeric MoDTC structures and complexes with a similar structure. 30 , 34 This phenomenon is due to the capability of the metallic substrate to stabilize more efficiently the fragments originating by separating the complexes between the chalcogen atoms and the carbon atom of the ligand unit. mMoDTC compounds follow the general rules derived for these small organometallic complexes While the fragmentation of isolated complexes is not favorable, the metallic substrate is able to stabilize the molecular fragments and the dissociation energies become favorable.…”
Section: Resultsmentioning
confidence: 99%
“…A 12 × 12 × 12 K-point grid was used to sample the Brillouin zone of the iridium bulk and the K-point grid was proportionally resized for all the following calculations. We chose not to add any dispersion correction, consistently with our previous investigations [ 56 57 ], because these corrections often overestimate the adsorption energies on metallic substrates [ 58 59 ]. The process of geometry optimization was stopped when the total energy and the forces converged under thresholds of 1 × 10 −4 Ry and 1 × 10 −3 Ry/bohr, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As seen from the later X-ray photoelectron spectroscopy (XPS) studies, the oxidation state of Co did not notably change during heating. Judging from the structural simplicity of Co­(II) acac 2 , and the noted strong acetylacetone smell, this change in color and exotherm should be related to the dissociation of acac – ligands, which were then protonated and escaped from the system in the form of Hacac gas. In the meantime, consistent with the UV–vis observation, an equimolar amount of TPP and Co­(II) acac 2 comixture (red) delayed the exotherm peak to above 125 °C.…”
Section: Resultsmentioning
confidence: 99%